Profile of teacher pedagogical competency - Jeki Haryanto; Salvetri Salvetri (Global Econedu, 2021)
The pedagogic competence of physical education teachers is still relatively low and needs to be improved so that students' understanding during learning takes place is better. The learning process that occurs in the classroom and outside the classroom should take place pleasantly, to realize this a good teacher is needed. This study aims to determine the level of pedagogic competence of physical education teachers from the point of view of the principal's assessment. This needs to be known in order to add insight into the pedagogical competence of teachers from various existing points of view, so that the understanding of the pedagogical competence of teachers can be more in-depth.Survey research was conducted to see the principal's assessment of the pedagogic competence of physical education teachers. The population in this study were all public elementary school sports teachers in Kerinci Regency, totaling 228 people. The sampling technique in this study used a simple random sampling technique so that 50 people were selected as samples. Data on the pedagogic competence of sports teachers in this study were collected using a questionnaire.The results of this study indicate that the level of pedagogic competence of sports teachers based on the principal's assessment is in the sufficient category. So that physical education teachers, school principals, and the government need to make programs so that the pedagogical competence of sports teachers can increase.